Balance of Payments Textbook. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
The Balance of Payments Textbook, like the Balance of Payments Compilation Guide, is a companion document to the fifth edition of the Balance of Payments Manual. The Textbook provides illustrative examples and applications of concepts, definitions, classifications, and conventions contained in the Manual and affords compilers with opportunities for enhancing their understanding of the relevant parts of the Manual. The Textbook is one of the main reference materials for training courses in balance of payments methodology.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet